EMPOWERING SPEAKING SKILLS THROUGH TASK-BASED INSTRUCTION IN HIGH SCHOOL STUDENTS - Fitriani Fitriani (PRIMACY Journal of English Education and Literacy, 2023)
As a lingua franca, English is utilized by most people in all parts of the world. In Indonesia, English teaching needs rejuvenation, restorations, and more in an attempt to reach the expected proceeds. When the condition is implemented, the moral probe is proposed to the English teachers to undertake the subject in a better and more effective way. Speaking skill plays the most prominent role in human communication. In teaching this skill, English teachers should pay more concern to make the student relish communicative competence which desires help the student to be able to communicate in spoken language communicatively. Nevertheless, teaching speaking is not a convenient task. EFL teachers find it troublesome to inform students to get involved in speaking skills. Several learners have the right capability in the grammar structure but they are not skilled in speaking communicatively. They are competent to speak with correct grammar but they are not powerful to say something suitable in the social context. Also, some other students are still misled in comprehending an individual message which is stated through spoken language. So, they have a low motivation to speak English. To help students attain communicative competence in speaking skills, English teachers can apply Task-Based Instruction (TBI) in the classroom. This paper aims to give an illustration of TBLT as an approach to improving speaking skills for students in High School. Also, as a solution for English teachers